EZH2 inhibits autophagic cell death of aortic vascular smooth muscle cells to affect aortic dissection - Li, Rui (Cell Death Dis, 2018)
Enhancer of zeste homolog 2 (EZH2), a methyltransferase that di- and tri-methylates lysine-27 of histone H3, largely functions as a transcriptional repressor, and plays a critical role in various kinds of cancers. Here we report a novel function of EZH2 in regulating autophagic cell death (ACD) of vascular smooth muscle cells (VSMCs) that affect aortic dissection (AD). Inhibition of EZH2 activity by UNC1999 or knockdown EZH2 resulted in VSMC loss, while overexpression of EZH2 facilitated VSMC growth, and these effects of EZH2 on VSMCs were independent of proliferation and apoptosis. Interestingly, more autophagic vacuoles and increased LC3II protein levels were identified in VSMCs with EZH2 inhibition or deficiency. Moreover, when compared with counterparts, chloroquine alone, or chloroquine with rapamycin treatment led to more LC3II accumulation in EZH2 inhibited or knockdown VSMCs, which indicated that EZH2 negatively regulated autophagosome formation. In conjunction to this, ATG5 and ATG7 protein levels were remarkably increased in EZH2 inhibited or deficient VSMCs, and ATG5 or ATG7 knockdown virtually rescued VSMC loss induced by EZH2 inhibition or knockdown. In addition, we found that the MEK–ERK1/2 signaling pathway, but not AMPKα, mTOR, or AKT pathway, is responsible for the impact of EZH2 on ACD of VSMCs. Additionally, the adverse effects of EZH2 inhibition or knockdown on VSMCs were largely reversed by PD98059, an inhibitor of MEK1. More importantly, decreased EZH2 expression levels in the aortic wall of patients with AD indicated its contribution to VSMC loss and AD occurrence. Overall, these findings revealed that EZH2 affects ACD of VSMCs and the pathologic process of AD via regulating ATG5 and ATG7 expression and MEK–ERK1/2 signaling. Our hitherto unrecognized findings indicate that EZH2 activation has therapeutic or preventive potential for AD.